EFEKTIFITAS PENGGUNAAN SINAR UV UNTUK PENYIMPANAN PERALATAN MEDIS PUSKESMAS - Bedjo Utomo; Endang Dian Setioningsih (Poltekkes Kemenkes Surabaya, 2014)
In general, this study analyzed the effectiveness of the use of UV light for the storage of medicalquipment in health centers by distance and time. This type of this research is experimental withre and post study design, particularly to analyze the effectiveness of UV light by distance and timef exposure. As the dependent variable in this study is the microorganisms and the independentariables are the factors of distance, time and design of medical devices storage size, while theontrol variable is the gelatin media. The results of UV light exposure at a distance 20 cm arebtained intensity of 15.8 Lumen and at a distance of 15 cm are obtained intensity of 11.2 Lumen.The average temperature that obtained during 3-hours exposure was at 35°C. Time effectivenessthat used to inhibit the growth of bacteria in the intensity of 15.8 lumen is 4 hours, while theintensity of 11.2 Lumen is 5-8 hours. Effectiveness analysis of the rate of growth of bacteria atintensity of 15.8 lumen using test probability 0.5% was obtained a significant value = 0.007 whereacterial samples of air quality (x2) is more effective than the kind of TBC bacteria (x). Theintensity at distance of 20 cm and 15 cm by using the Mann Whitney test it is obtained statisticalues  = 0.513 0.05 where there is no statistical difference between these two intensity withthe rate of growth of bacterial colonies.In general, the results of this study can be concluded thatUV exposure can be used as a sterilizer on the storage of medical equipment in health centers thatimple by taking into account the factors of UV light time and intensity. Keywords:Effectiveness, UV light, sterilization, storage equipment, medical equipment 1